Механізми фінансування відтворення житлового фонду і ринок будівельних робіт - Жураковська, М. О. (Ways to Improve Construction Efficiency, 2013)
The public policy in capital repairs, state of housing stock is analyzed, financial mechanisms of housing stock and capital repairs renovation are defined, effective management of the housing stock is proposed.